Longitudinal parallel compression suture to control postopartum hemorrhage due to placenta previa and accrete - Guang-Tai Li; Xiao-Fan Li; Baoping Wu; Guangrui Li (Elsevier, 2016)
Objective: To assess the efficacy and safety of longitudinal parallel compression suture to control heavy postpartum hemorrhage (PPH) in patients with placenta previa/accreta. Materials and Methods: Fifteen women received a longitudinal parallel compression suture to stop life-threatening PPH due to placenta previa with or without accreta during cesarean section. The suture apposed the anterior and posterior walls of the lower uterine segment together using an absorbable thread A 70-mm round needle with a Number-1 absorbable thread was used. The point of needle entry was 1 cm above the upper margin of the cervix and 1 cm from the right lateral border of the lower segment of the anterior wall. The suture was threaded through the uterine cavity to the serosa of the posterior wall. Then, it was directed upward and threaded from the posterior to the anterior wall at ∼1-2 cm above the upper boundary of the lower uterine segment and 3-cm medial to the right margin of the uterus. Both ends of the suture were tied on the anterior aspect of uterus. The left side was sutured in the same way. Results: The success rate of the procedure was 86.7% (13/15). Two of 15 cases were concurrently administered gauze packing and achieved satisfactory hemostasis. All patients resumed a normal menstrual flow, and no postoperative anatomical or physiological abnormalities related to the suture were observed. Three women achieved further pregnancies after the procedure. Conclusion: Longitudinal parallel compression suture is a safe, easy, effective, practical, and conservative surgical technique to stop intractable PPH from the lower uterine segment, particularly in women who have a cesarean scar and placenta previa/accreta.